The measurement of serum osmolality and its application to clinical practice and laboratory: literature review - Daniel K. Faria; Maria Elizabete Mendes; Nairo M. Sumita
ABSTRACT Introduction: Serum osmolality is an essential laboratory parameter to understand several clinical disorders such as electrolyte disturbances, exogenous intoxication and hydration status. Objective: This study aims to update knowledge about the osmolality examination through research papers published to date. Materials and methods: The survey was conducted on PubMed database. It highlights main concepts, both historical and physiological aspects, and the clinical applications of the serum osmolality test. In addition, an extensive survey of formulas for the serum osmolality calculation was conducted. Discussion: The measurement of serum osmolality is relevant in changes in intracellular and extracellular balance, as a trusted and valuable indicator of solute concentration in the blood. The mathematical equations for serum osmolality calculation acquire relevance in health services where serum is not available, and situations in which calculation of the osmolal gap is necessary, but the variability of the formulas is a significant bias. Conclusion: The measurement of serum osmolality is useful in cases of dehydration, sodium and potassium disorders, glucose alteration, exogenous poisoning, adrenal insufficiency, neurological injury, physical exercise and others.